2015
DOI: 10.1590/0104-1169.0185.2529
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about breast cancer and hereditary breast cancer among nurses in a public hospital

Abstract: OBJECTIVE: To assess the knowledge of nurses involved in the care of oncology patients in a public university hospital, regarding breast cancer and hereditary breast cancer, and to verify the use of such knowledge in their daily practice. METHODS: This is a descriptive cross-sectional study. Data were obtained through a structured, self-administered questionnaire. Out of 154 nurses, 137 (88.9%) agreed to participate in the study. Two questionnaires were excluded such that 135 questionnaires were analyzed. RESU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 17 publications
(19 reference statements)
1
25
0
6
Order By: Relevance
“…Lack of knowledge about actions for screening was also found in one study of nurses working at a public hospital in the southern state of Rio Grande do Sul, in which the authors concluded that the nurses were not familiar with the protocols defined by the MOH, nor priority programs such as control of breast cancer (19) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lack of knowledge about actions for screening was also found in one study of nurses working at a public hospital in the southern state of Rio Grande do Sul, in which the authors concluded that the nurses were not familiar with the protocols defined by the MOH, nor priority programs such as control of breast cancer (19) .…”
Section: Discussionmentioning
confidence: 97%
“…Rev Esc Enferm USP · 2016;50(1): [14][15][16][17][18][19][20][21] women aged between 40 and 69 years. This protocol is in accordance with the guidelines of the Brazilian Society of Mastology, which diverges from that of the MOH.…”
Section: Discussionmentioning
confidence: 99%
“…Para los antecedentes de morbilidad se descubrió que la totalidad de las pacientes poseen antecedentes de cáncer. Al respecto, el estudio de Prolla et al (27) revelo que "el cáncer de mama es una enfermedad multifactorial en la que los factores genéticos y ambientales contribuyen a su aparición".…”
Section: Discussionunclassified
“…A neoplasia maligna da mama é o câncer mais incidente e a segunda causa de óbito em todo o mundo em mulheres (1) . No Brasil, as estimativas para o ano de 2016 indicam que 57.960 casos novos de neoplasia maligna da mama feminino serão detectados.…”
Section: Introductionunclassified
“…O diagnóstico da neoplasia maligna da mama, comumente, é avassalador na vida da mulher que o recebe, seja pelo medo das mutilações e tratamentos agressivos, seja pelo medo de morrer ou pelas múltiplas perdas, no que tange aos aspectos social, econômico e psicológico, o que na maioria das vezes acontece (4)(5) . As pessoas com câncer de mama precisam de apoio emocional e, algumas vezes, apenas de uma palavra de conforto, um abraço, um pouco de atenção ou somente de um indivíduo que as escute sobre seus medos, dúvidas ou perspectiva de vida, ou seja, um cuidado humanizado (1,3) .…”
Section: Introductionunclassified